Cardiovascular Diseases in Dhulikhel Hospital - koju, R; Dongol, S; Pokhrel, A; Karmacharya, B; Takhacche, S (Nepalese Heart Journal, 2004)
Dhulikhel Hospital is a non-profit community hospital located in Dhulikhel, 30 km east of Kathmandu, providing services to Kavrepalanchowk and other surrounding districts of nearly 1.2 million people since 1996. The hospital is providing services of medical, surgical, obstetric and gynecological, pediatric and other services.